The model of Mary’s faith in the Wedding at Cana (Jn 2:1-12): Gương mẫu đức tin của Đức Maria trong Tiệc cưới Cana (Ga 2: 1-12) - Nguyen, Xuan Cuong (Khoa Học Công Giáo và Đời Sống, 2022)
Faith is essential for Christians on the journey of grace to follow God and reach out to others. In flourishing their faith, they can find precious help from Mary's example of faith in the wedding at Cana, which is full of humility and positively waiting for God's will.